Cryptococcosis in wait-listed liver transplant candidates: Prevalence, manifestations, and risk factors - Wan-Ting Tsai; Aristine Cheng; Yu-Chung Chuang; Cheng-Maw Ho; Yao-Ming Wu; Ming-Chih Ho; Hsin-Yun Sun; Ray-Hung Hu; Yee-Chun Chen (Journal of Microbiology, Immunology and Infection)
Background: Liver cirrhosis compromises immunity against cryptococcosis, and liver transplant recipients tend to develop the disease earlier after transplantation, possibly due to unrecognized pretransplant infection. We assessed the prevalence and characteristics of cryptococcosis among liver transplant candidates and whether pre-transplant cryptococcal antigen (CrAg) can detect the disease before transplantation. Methods: We retrospectively included liver transplant candidates in a tertiary hospital during 2017–2022. Serum CrAg and pulmonary computed tomography were incorporated in routine transplant evaluation. Other investigations were done if indicated. Cryptococcosis was diagnosed by positive culture or CrAg. Risk factors for cryptococcosis were also assessed. Results: Of the 377 candidates with a median MELD-Na score of 18, 84.4% had hepatitis B virus (HBV) infection. Cryptococcosis was diagnosed in 10 (2.6%) candidates, by CrAg in 6, culture in 2, or both in 2. Only 3 had fever, and 3 were asymptomatic; 7 had pulmonary cryptococcosis. Of the 10 candidates with cryptococcosis, one underwent transplantation after 143-day antifungals. Of the 87 candidates undergoing liver transplantation, one (1.2%) recipient developed cryptococcosis 14 days post-transplant with negative CrAg three weeks before transplantation. HBsAg-positive chronic HBV infection with HBV DNA loads <2000 IU/mL was significantly associated with cryptococcosis (odds ratio 4.4, 95% confidence interval 1.2–16.5, p = 0.03) after the adjustment of MELD-Na score. Conclusions: The prevalence of cryptococcosis was 2.6% among our liver transplant candidates and CrAg detected 80% of the cases. Disease presentation was mild and pulmonary disease predominated. HBsAg-positive chronic HBV infection with HBV DNA loads <2000 IU/mL was significantly associated with cryptococcosis.